Manufacture of the Functional Noodle and its Effects on Postprandial 2h-blood Glucose and Serum Lipid Levels of Subjects with IGT - Kim, Yong-Taek; Jo, Zong-Do; Pang, Hung-Mun; Paek, Chan-Ok; Mun, Chang-Sok (Current Nutrition & Food Science, 2020)
Background: The earliest determinant of progression to type 2 diabetes is a loss of early insulin secretion, a defect which results in postprandial hyperglycemia and is often believed to reflect insulin resistance. In Asian countries including our country, noodle is the traditional food which has been eaten from ancient times and is taken one or two times a day. The functional noodle is a staple meeting nutritional requirements for the prevention and treatment of Impaired Glucose Tolerance (IGT). Methods: FNs were prepared using the noodle making machine according to Barak et al. with slight modifications. After giving FNs prepared by three mixing ratios of main materials to the IGT-induced rats for 30 days, the levels of postprandial 2h-blood glucose in all experimental groups and control group were measured to determinate the optimal mixing ratio of FN. After the IGT subjects in experimental group ate 200g of FN (dried weight) in exchange for a lunch for 60 days, the levels of postprandial 2h-blood glucose and of TG and TC in serum were measured to compare with that in the control group who had not undergone control in their diet. Result: After 30 days of experiment, the levels of postprandial 2h-blood glucose in rats of pl group 4 were lowest. The levels of postprandial 2h-blood glucose in the control group that most of them had not undergone control in their diet were increased, but that in experimental group who had taken FN decreased from 30 days of experiment to be significantly different after 60 days. The concentrations of serum TC and TG of IGT subjects in the experimental group were decreased compared with that in the control group, but significance among two groups was achieved only in the concentration of serum TC. Conclusion: FN made in the 4:3:3 ratio of powder of corn, powder of bean cake defatted and powder of peeled whole potato is more effective to decrease the levels of postprandial 2h-blood glucose. FN is a staple type of functional food that could be used for the treatment of IGT.
Keywords: type 2 diabetes